Analysis of Characteristics of Roof Fall Collapse of Coal Mine in Qinghai Province, China - Wang, Ya-Jie; Zhao, Lin-Shuang; Xu, Ye-Shuang (Applied sciences, 2022)
This paper presents the roof fall collapse of a coal mine that occurred, causing 20 deaths and 1 injury, in Qinghai Province, China, on 14 August 2021. After the primary investigation of this incident and a brief description of the rescue action undertaken, this report discussed the possible reasons behind this disaster. The fissure water and damaged rock mass are the dominant triggering factors of this incident. Little concern for risk assessment and monitoring systems is one of the main man-made mistakes. Consequently, the reflections and suggestions are put forward to reduce or prevent the occurrence of roof fall incidents in coal mines. The noteworthy actions that are necessary in coal mine projects are conducting risk assessments based on geological condition and building proper support systems for coal mines considering he situation in situ.